2011
DOI: 10.1097/icl.0b013e318235893a
|View full text |Cite
|
Sign up to set email alerts
|

Alcaligenes xylosoxidans Contact Lens–Related Keratitis—A Case Report and Literature Review

Abstract: Alcaligenes xylosoxidans is a potential pathogen in compromised corneas. It has high susceptibility to extended-spectrum penicillins and current generations of fluoroquinolones but rarely responds to aminoglycosides. Alcaligenes xylosoxidans should be considered in the differential diagnosis of contact lens-induced keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…[2, 20] Previous studies have also reported ocular infections by A. xylosoxidans in immunocompetent patients. [5, 8, 10, 1213, 19] Cataract surgery was the only risk factor associated in the current study. Therefore, there were no known risk factors to distinguish between ocular infections with A. xylosoxidans versus other more common isolates.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…[2, 20] Previous studies have also reported ocular infections by A. xylosoxidans in immunocompetent patients. [5, 8, 10, 1213, 19] Cataract surgery was the only risk factor associated in the current study. Therefore, there were no known risk factors to distinguish between ocular infections with A. xylosoxidans versus other more common isolates.…”
Section: Discussionmentioning
confidence: 55%
“…[3] This organism is known to cause both acute-onset and delayed-onset postoperative endophthalmitis. [411] Previous reports have also documented A. xylosoxidans keratitis in contact lens wearers [1213]. …”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4,5,6 Acanthamoeba spp. are free-living protozoan parasites and are particularly reported to be associated with poor hygienic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…are gram-negative, aerobic bacilli; although rare, they may cause keratitis, particularly in compromised corneas. 5,6 …”
Section: Discussionmentioning
confidence: 99%